2017
DOI: 10.1088/1748-3190/12/1/011002
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetics: process, tools and practice

Abstract: Biomimetics applies principles and strategies abstracted from biological systems to engineering and technological design. With a huge potential for innovation, biomimetics could evolve into a key process in businesses. Yet challenges remain within the process of biomimetics, especially from the perspective of potential users. We work to clarify the understanding of the process of biomimetics. Therefore, we briefly summarize the terminology of biomimetics and bioinspiration. The implementation of biomimetics re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(166 citation statements)
references
References 56 publications
1
164
0
1
Order By: Relevance
“…The results of this research have led to a framework of the usage of tools. 92 Furthermore, ongoing research will help to assess the value of tools for certain problems, contexts and desired aims of the process -for instance, the aim for a functional optimisation of products or for a more sustainable product development. The following research questions will be addressed in the future.…”
Section: Use Of Tools In Practice and Outlookmentioning
confidence: 99%
“…The results of this research have led to a framework of the usage of tools. 92 Furthermore, ongoing research will help to assess the value of tools for certain problems, contexts and desired aims of the process -for instance, the aim for a functional optimisation of products or for a more sustainable product development. The following research questions will be addressed in the future.…”
Section: Use Of Tools In Practice and Outlookmentioning
confidence: 99%
“…Compared with the solution-driven process, the problem-driven process is much more similar to the conceptual design process. With successive development [89], an eight-stage unified problem-driven biomimetics process is proposed to represent a highly systemic and practical BID process as discussed in Fig. 4(c).…”
Section: Design Algorithms For Biologically Inspired Innovationmentioning
confidence: 99%
“…A recent review [8] identified The functional approach has long been a key central concept to the practice of biomimicry and has been identified as a solution to overcome the difficulties of its interdisciplinary nature. A recent review of biomimetic tools and processes identified several models of the problem-driven approach and correlated them with the general problem-solving process of Massay & Wallace 1956 [13], commonly used in engineering and design [12]. Of the 12 biomimetic processes identified, half clearly state a functional step referred to as either function identification and definition [14][15][16], functional keyword searches [17,18] or functional modeling [19].…”
Section: Figurementioning
confidence: 99%
“…Illustration of the traditional problem-driven biomimicry design process and steps that selected tools facilitate. E2B Thesaurus (Step 2 and 3) and BioMimetic Ontology (Step 2 to 7)[12].…”
mentioning
confidence: 99%